2021
DOI: 10.5964/jspp.7539
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup threat and affective polarization in a multi-party system

Abstract: What explains affective polarization among voters and societal groups? Much of the existing literature focusing on mass political polarization in modern democracies originates in the US, where studies have shown that, while ideological separation has grown, political conflict increasingly reflects social identity divisions rather than policy disagreements, resulting in affective polarization. We focus on explaining such polarization in a multi-party context. Drawing on social identity theory and intergroup thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 36 publications
(42 reference statements)
2
34
1
Order By: Relevance
“…In contrast, negative like-dislike ratings can be accompanied by a wide range of partisan social distance scores, and quite often people who dislike a party profess indifference toward its supporters. We have not seen this asymmetry reported by others who have investigated partisan-directed attitudes (e.g., Knudsen, 2020;Renström et al, 2021). We do not know whether this is because they have found it uninteresting or because it is a feature particular to our data.…”
Section: The Puzzle Of Attitudes Toward Parties and Attitudes Toward ...contrasting
confidence: 81%
See 1 more Smart Citation
“…In contrast, negative like-dislike ratings can be accompanied by a wide range of partisan social distance scores, and quite often people who dislike a party profess indifference toward its supporters. We have not seen this asymmetry reported by others who have investigated partisan-directed attitudes (e.g., Knudsen, 2020;Renström et al, 2021). We do not know whether this is because they have found it uninteresting or because it is a feature particular to our data.…”
Section: The Puzzle Of Attitudes Toward Parties and Attitudes Toward ...contrasting
confidence: 81%
“…Data on partisandirected attitudes, however, is comparatively limited. Knudsen (2020) and Renström et al (2021) have used the familiar "Social distance", as used in the literature, has two slightly di erent meanings. Iyengar et al ( ) use it to refer to partisan-directed attitudes more generally, whereas, Druckman and Levendusky ( ) use the term more specifically to refer to feelings of comfort with having outparty partisans in one's social circles, i.e., an application of Bogardus's ( ) social distance scale.…”
Section: Theorymentioning
confidence: 99%
“…As mentioned, we add to the literature on the causes of affective polarization by arguing that the perceived threats toward the individual's ingroup can spur such partisan hostilities and bias (see also Renström et al, 2021). In line with the findings of the previous literature, we recognize that both identity and ideology are important determinants of the affective polarization.…”
Section: Theoretical Frameworksupporting
confidence: 65%
“…First, several authors have shown that strengthening group identification increases affective polarization (Iyengar et al, 2012;Mason, 2015;Webster and Abramowitz, 2017;Reiljan and Ryan, 2021). Second, numerous studies show that individuals become increasingly affectively polarized as their views become more ideologically extreme (Webster and Abramowitz, 2017;Harteveld, 2021;Lelkes, 2021;Renström et al, 2021). While both identity and ideology are known to be important drivers of affective polarization, our findings suggest that the perceived threats toward the individual's ingroup can spur affective polarization (see also Rogowski and Sutherland, 2016).…”
Section: Introductionmentioning
confidence: 46%
See 1 more Smart Citation